2022
DOI: 10.20491/isarder.2022.1518
|View full text |Cite
|
Sign up to set email alerts
|

Jeopolitik Riskin Pay Senedi Fiyatlarına Etkisinin Fourier Yaklaşımıyla Değerlendirilmesi: Türkiye Örneği(Evaluation with Fourier Approach of the Effect of Geopolitical Risk on Stock Prices: The Case of Turkey)

Abstract: Amaç –Finansal serbestleşme süreci uluslararası sermaye akımlarını hızlandırmıştır. Ancak ülkelerde belli dönemlerde ortaya çıkan birtakım ekonomik ve siyasi belirsizlikler sonucunda finansal hareketlilik yavaşlamaktadır. Türkiye’nin siyasi ve ekonomik yönden bağlantılı olduğu ülkelerde son yıllarda yaşanan askeri çatışmalar, ekonomik krizler, politik ve toplumsal huzursuzluklar gibi birçok faktörün Türkiye’deki ekonomik faaliyetlerin gelişimini ve yatırım hacmini olumsuz etkilediği yönünde bir kanaat hakimdi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Because, together with the Arab Spring, terrorist incidents, wars and internal turmoil in the geography of Turkey have significantly affected the geopolitical risk level of the country in question. The developments in this process have shown that the risk factors around Turkey have changed the economic and political structure of the country (Gülcan & Ceyhan, 2022). This situation also disrupts the tourism sector, which makes a great contribution to the economy of a developing country like Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…Because, together with the Arab Spring, terrorist incidents, wars and internal turmoil in the geography of Turkey have significantly affected the geopolitical risk level of the country in question. The developments in this process have shown that the risk factors around Turkey have changed the economic and political structure of the country (Gülcan & Ceyhan, 2022). This situation also disrupts the tourism sector, which makes a great contribution to the economy of a developing country like Turkey.…”
Section: Introductionmentioning
confidence: 99%